Revitalisasi Nilai-Nilai Pancasila Melalui Pembelajaran PKN Berbasis Kearifan Lokal untuk Penguatan Karakter dan Jati Diri Bangsa - Sumardjoko, Bambang (Jurnal VARIDIKA, 2013)
General purpose of the research is to find and develop Pkn learning model at Junior High School bases local wise for revitalization pancasila values strategy to strength character and self characteristic country. This research is for two years. The first year, the research is qualitative research. Collecting data technique are interview, attentively method and observation. Analysis data uses interactive method. Focus prob- lem reviews and planning draft model uses qualitative approach with pathways: (1) lit- erature study, collecting materials support relationship Pkn learning model, (2) field data colleting and triangulation data descript PKn learning model at Junior High School implementation, (3) SWOT analysis constructs draft model, and (4) refining design mod- el (tentative) by workshop participation-collaborative. Result of the research shows (1) Profile background PKn teachers at Junior High School of Surakarta are PKn education and they have experience teach a long time. (2) PKn teachers have experience in scien- tific activities in local or national so understanding PKn teachers Junior High School of Surakarta about the primary and purpose of citizenship education is enough good. (3) To development PKn learning is powerfull it needs revision to PKn material, the primary about (a) integration local culture value and (b) strategy and learning method support mastery competent PKn and education value. (4) According SWOT analysis, draft de- velops PKn model in Junior High School bases local wise for revitalization strategy Pancasila values to strength character and self characteristic of country with (a) wise integration local java culture source from core value esteem, social problem solving, study with social interaction and study with interaction social-culture, (c) implementa- tion draft model with problem based learning model, project based learning and value classification.